The fungicide pyraclostrobin affects gene expression by altering the DNA methylation pattern in Magnaporthe oryzae - Fang, Shumei; Wang, Hanxin; Qiu, Kaihua; Pang, Yuanyuan; Li, Chen; Liang, Xilong (Frontiers in Plant Science, 2024)
Rice blast disease caused by Magnaporthe oryzae has long been the main cause of rice (Oryza sativa L.) yield reduction worldwide. The quinone external inhibitor pyraclostrobin is widely used as a fungicide to effectively control the spread of pathogenic fungi, including M. oryzae.However, M. oryzae can develop resistance through multiple levels of mutation, such as target protein cytb mutation G143A/S, leading to a decrease in the effectiveness of the biocide after a period of application. Therefore, uncovering the possible mutational mechanisms from multiple perspectives will further provide feasible targets for drug development. In this work, we determined the gene expression changes in M. oryzae in response to pyraclostrobin stress and their relationship with DNA methylation. The results showed that under pyraclostrobin treatment, endoplasmic reticulum (ER)-associated and ubiquitin-mediated proteolysis were enhanced, suggesting that more aberrant proteins may be generated that need to be cleared.DNA replication and repair processes were inhibited. Glutathione metabolism was enhanced, while lipid metabolism was impaired. The number of alternative splicing events increased. These changes may be related to the elevated methylation levels of cytosine and adenine in gene bodies. Both hypermethylation and hypomethylation of differentially methylated genes (DMGs) mainly occurred in exons and promoters. Some DMGs and differentially expressed genes (DEGs) were annotated to the same pathways by GO and KEGG, including protein processing in the ER, ubiquitin-mediated proteolysis, RNA transport and glutathione metabolism, suggesting that pyraclostrobin may affect gene expression by altering the methylation patterns of cytosine and adenine in gene bodies. Our results revealed that 5mC and 6mA in the gene body are associated with gene expression and contribute to adversity adaptation in M. oryzae. This enriched the understanding for potential mechanism of quinone inhibitor resistance, which will facilitate the development of feasible strategies for maintaining